Structural and functional characteristics and expression profile of the 20S proteasome gene family in Sorghum under abiotic stress - Malik, Vijai; Ikram, Faiza Mohamad; Singh, Yogita; Kumar, Vivek; Malik, Pranita; Balyan, Priyanka; Singh, Krishna Pal; Mir, Reyazul Rouf; Hashem, Abeer; Avila-Quezada, Graciela Dolores; Abd_Allah, Elsayed Fathi; Kumar, Upendra (Frontiers in Plant Science, 2023)
The 26S proteasome is a molecular machine that catalyses and degrades protein intracellularly with the help of its core complex called 20S proteasome. The 20S proteasomes degrade and cleave, denatured, cytotoxic, damaged and unwanted proteins via proteolysis and impart biotic and abiotic stress tolerance in model plants. This study identified 20 genes, including 10 SbPA and 10 SbPB that encode for α and β-subunits of the 20S proteasome in Sorghum bicolor (L.) Moench (2n= 20). These genes have been found distributed on 1, 2, 3, 4, 5, 7, and 10th chromosomes. These sorghum genes were orthologous to corresponding rice. Phylogenetic analysis clustered these genes into seven clades, each with one of the seven α (1 to 7) and one of the seven β (1 to 7) subunits. In-silico Gene expression analysis suggested that nine genes were involved in abiotic stress response (Cold, drought, and Abscisic acid hormone). The expression of these proteasomal genes was studied in shoots and roots exposed to different abiotic stresses (cold, drought, and abscisic acid) by quantitative real-time polymerase chain reaction. A significant increase in the relative fold expression of SbPBA1, SbPAA1, SbPBG1, SbPBE1 and SbPAG1 genes under ABA and drought stress provides an insight into its involvement in abiotic stress. No expression was observed for cold stress of these genes indicating their non-involvement. It is believed that additional investigation into the SbPA/SbPB genes would aid in the creation of S. bicolor cultivars that are resistant to climate change.